A new species of Menestho Møller, 1842 from the Arctic with remarks on Menestho albula (Fabricius, 1780)(Gastropoda: Heterobranchia: Pyramidellidae) - NEKHAEV, IVAN O. (Zootaxa, 2017)
North Atlantic and Arctic representatives of the family Pyramidellidae had been intensively studied during the last decades. A valuable contribution was made by Warén (1989; 1991; 1993), who partially revised several genera from the Scandinavian waters. Norwegian representatives of the family were reviewed by Høisæter (2014). Distribution and diagnostic of many species had been specified by Schander (1995) and Nekhaev (2011; 2014; 2017). However, in the Eurasian Arctic Seas (except for the SW Barents Sea) only five species of Pyramidellidae had been recorded (Golikov et al. 2001; Kantor & Sysoev 2006; Nekhaev 2017): Liostomia eburnea (Stimpson, 1851), Chrysallida sublustris (Friele, 1886), Amaura candida (Møller, 1842), Amaura arctica (Dall et Bartsch, 1909) and Menestho truncatula Odhner, 1915.